α-Mangostin Alleviated HIF-1α-Mediated Angiogenesis in Rats With Adjuvant-Induced Arthritis by Suppressing Aerobic Glycolysis - Jiang, Tian-Tian; Ji, Chao-Fan; Cheng, Xiu-Ping; Gu, Shao-Fei; Wang, Rui; Li, Yan; Zuo, Jian; Han, Jun (Frontiers in Pharmacology, 2021)
A previously validated anti-rheumatic compound α-mangostin (MAN) shows significant metabolism regulatory effects. The current study aimed to clarify whether this property contributed to its inhibition on synovial angiogenesis. Male wistar rats with adjuvant-induced arthritis (AIA) were orally treated by MAN for 32 days. Afterwards, biochemical parameters and cytokines in plasma were determined by corresponding kits, and glycometabolism-related metabolites were further accurately quantified by LC-MS method. Anti-angiogenic effects of MAN were preliminarily assessed by joints based-immunohistochemical examination and matrigel plug assay. Obtained results were then validated by experiments in vitro. AIA-caused increase in circulating transforming growth factor beta, interleukin 6, hypoxia inducible factor-1 alpha (HIF-1α) and vascular endothelial growth factor (VEGF) in blood and local HIF-1α/VEGF expression in joints was abrogated by MAN treatment, and pannus formation within matrigel plugs implanted in AIA rats was inhibited too. Scratch and transwell assays revealed the inhibitory effects of MAN on human umbilical vein endothelial cells (HUVECs) migration. Furthermore, MAN inhibited tubule formation capability of HUVECs and growth potential of rat arterial ring-derived endothelial cells in vitro. Meanwhile, MAN eased oxidative stress, and altered glucose metabolism in vivo. Glycolysis-related metabolites including glucose 6-phosphate, fructose 6-phosphate, 3-phosphoglyceric acid and phosphoenolpyruvic acid in AIA rats were decreased by MAN, while the impaired pyruvate-synthesizing capability of lactate dehydrogenase (LDH) was recovered. Consistently, MAN restored lipopolysaccharide-elicited changes on levels of glucose and LDH in HUVECs culture system, and exerted similar effects with LDH inhibitor stiripentol on glycometabolism and VEGF production as well as tubule formation capability of HUVECs. These evidences show that MAN treatment inhibited aerobic glycolysis in AIA rats, which consequently eased inflammation-related hypoxia, and hampered pathological neovascularization.